Social Service Providing Basic Food Assistance As A Form Of Higher Education Service To The Community At The Said Muhammad Abu Bakar Al-Jupri Batam Foundation And The Al-Jufri Orphanage Orphanage - Haufi Sukmamedian; Andri Wibowo; Yudha Wardani; Tirta Mulyadi; Dailami; Wahyudi Ilham; Agung Edy Wibowo; M. Sani Al Fikri (JURNAL KEKER WISATA, 2026)
Community Service Activities (PKM) with the title "Social Service for the Distribution of Basic Necessities" is a form of social concern that aims to help people in need, especially in meeting daily basic needs. This activity is carried out by distributing food packages to underprivileged communities, orphanages, or other vulnerable groups. The implementation of activities is carried out through the planning stages, collecting data on beneficiaries, and distributing aid directly so that it is right on target. In addition, this activity also involves the active participation of students, lecturers, and related parties as a form of implementation of the values of mutual cooperation and social concern. The results of this activity show that the assistance provided can ease the economic burden on the community and strengthen the relationship between universities and the community. This activity also provides real experience for students in implementing humanitarian values and service. Thus, this PKM activity is expected to provide short-term benefits in the form of assistance for basic needs, as well as long-term benefits in the form of increased empathy, social solidarity, and concern for others in community life.